TINJAUAN KONSEPTUAL MAKRO-MIKRO PEMASARAN DAN IMPLIKASINYA BAGI PEMBANGUNAN PERTANIAN (Forum Penelitian Agro Ekonomi, 2024)
Economists are interested in the marketing concept try to apply it in agricultural development. Marketing concept has several aspects, i.e. economy, business, and policy. Some people interpret marketing concept in terms of macro aspect (national level) and micro aspect (firm level). This paper proposes to examine marketing concept in term of macro and micro levels. Examining the marketing aspect at macro level will be useful to increase the marketing efficiency of agricultural commodity at regional or national level. It will also improve marketing efficiency in supply chain of agricultural commodity. Reviews on empirical studies indicate that some agricultural commodities have low marketing efficiency causing low competitiveness in the domestic and global markets. Enhancing marketing efficiency requires government intervention intended to reduce market distortion and high transaction cost in the supply chain of agricultural commodity. To achieve marketing efficiency of agricultural commodity, it is necessary to integrate macro-economic policy and micro-economic activities in the supply chain of agricultural commodity.